Liver Transplantation for Hepatic Trauma: A Study From the European Liver Transplant Registry. Issue 11 (November 2016) - Krawczyk, Marek; Grąt, Michał; Adam, Rene; Polak, Wojciech G.; Klempnauer, Jurgen; Pinna, Antonio; Di Benedetto, Fabrizio; Filipponi, Franco; Senninger, Norbert; Foss, Aksel; Rufián-Peña, Sebastian; Bennet, William; et al.
Abstract : Background: Liver transplantation is the most extreme form of surgical management of patients with hepatic trauma, with very limited literature data supporting its use. The aim of this study was to assess the results of liver transplantation for hepatic trauma. Methods: This retrospective analysis based on European Liver Transplant Registry comprised data of 73 recipients of liver transplantation for hepatic trauma performed in 37 centers in the period between 1987 and 2013. Mortality and graft loss rates at 90 days were set as primary and secondary outcome measures, respectively. Results: Mortality and graft loss rates at 90 days were 42.5% and 46.6%, respectively. Regarding general variables, cross-clamping without extracorporeal veno-venous bypass was the only independent risk factor for both mortality ( P = 0.031) and graft loss ( P = 0.034). Regarding more detailed factors, grade of liver trauma exceeding IV increased the risk of mortality ( P = 0.005) and graft loss ( P = 0.018). Moreover, a tendency above the level of significance was observed for the negative impact of injury severity score (ISS) on mortality ( P = 0.071). The optimal cut-off for ISS was 33, with sensitivity of 60.0%, specificity of 80.0%, positive predictive value of 75.0%, and negative predictive value of 66.7%. Conclusions: Liver transplantation seems to be justified in selected patients with otherwise fatal severe liver injuries, particularly in whom cross-clamping without extracorporeal bypass can be omitted. The ISS cutoff less than 33 may be useful in the selection process. Abstract : Hepatic trauma is a rare indication for liver transplantation. This collection of cases from the European Liver Transplant Registry provides guidance for indications and results demonstrating improved outcomes over time. Supplemental digital content is available in the text.